Kebahagiaan Lansia di Panti Sosial - Agnestiani Batzeba Mbeo; M. K. P. Abdi Keraf; Dian Lestari Anakaka (Journal of Health and Behavioral Science, 2019)
Living the life happily becomes a dream for every elderly. The purpose of this research is to obtain an overview of the happiness of the elderly. This research uses a phenomenological as one of the qualitative method. Three elderly from Panti Sosial Budi Agung Kupang participated. The data were collected using interview and observation techniques. Triangulation is carried out to check the validity of the data. The collected data is analyzed by reducing the data, creating themes, and validating the themes. The results showed that all the participants were happy at Panti Sosial Budi Agung Kupang.